PENGARUH CUSTOMERS RELATIONSHIP MANAGEMENT DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP CUSTOMER LOYALTY DENGAN COMPETITIVE ADVANTAGE DAN BRAND IMAGE SEBAGAI VARIABEL INTERVENING DI STARBUCKS SURABAYA - Hadi Setio (Jurnal Strategi Pemasaran, 2015)
The growth of the upper class society in Indonesia increased, leading to increased demand and supply of coffee dibisnis, especially the second largest metropolitan city of Surabaya. In Surabaya, the culture of drinking coffee in a cafe classy began to spread. The emergence of new cafes with the same concept to the competition in the coffee business is becoming increasingly heavy, how do Starbucks cafes to remain persaing win in the increasingly severe.market research aimed to analyze the influence of customers relationship management and corporate social responsibility towards Customer loyalty with Competitive advantage and brand image as an intervening variabel in Starbucks Surabaya.This study will be conducted by distributing questionnaires to 100 respondents consumers Starbucks Surabaya. Analysis technique used is quantitative analysis techniques.